Comparative photophysical and femtosecond third-order nonlinear optical properties of novel imidazole substituted metal phthalocyanines. (January 2021) - Bhattacharya, Somdatta; Reddy, Govind; Paul, Sneha; Hossain, Sk Saddam; Kumar Raavi, Sai Santosh; Giribabu, Lingamallu; Samanta, Anunay; Soma, Venugopal Rao
Abstract: Two novel phenanthro [9, 10-d]imidazole substituted metal phthalocyanines, ImCuPc and ImZnPc, have been synthesized and their potential as photosensitizers has been investigated through optical, electrochemical, and ultrafast nonlinear optical (NLO) studies, including their excited state dynamics. The absorption as well as emission spectra of both the title compounds exhibited negligible Stokes shift in different solvents. The molecules depicted a broad Soret band due to the incorporation of phenanthro[9, 10-d]imidazole moiety while the Q-bands were characteristic to their metal phthalocyanine group. DFT studies elucidated the HOMO-LUMO (4.99–2.90 eV) levels of these molecules with their energy optimized structures generated using DFT, TD-DFT analysis. The fs-TAS spectra of both the molecules exhibited contribution from singlet-singlet excited state absorption followed by transition to triplet states via intersystem crossing, ISC. The lifetimes calculated from obtained kinetics at specific wavelengths using global fitting demonstrated slow singlet to triplet state intersystem crossing in ImCuPc (decay rate of 1.6 × 10 8 s −1 ) and ImZnPc (decay rate of 1.4 × 10 8 s −1 ). The ns-TAS studies established long lived triplet states in both the molecules with ImCuPc depicting a slightly higher triplet lifetime of ~1.4 μs over ImZnPc with a triplet lifetime of ~1.2 μs The triplet quantum yields (φT ) were calculated to be 0.51 for ImCuPc while it was 0.27 for ImZnPc suggesting ImCuPc to be a better photosensitizer (PS) over ImZnPc. We believe the intramolecular D-π-A interaction is stronger in ImCuPc resulting in higher triplet yield. Third-order NLO studies performed at a non-resonant excitation of 800 nm (~50 fs, 1 kHz pulses) demonstrated ImZnPc had a larger two-photon absorption cross-section (994 GM), possibly due to heavy atom effect, while ImCuPc was found to possess superior n2 (3.7 × 10 −15  cm 2 /W). The slightly superior nonlinear optical (NLO) performance of ImCuPc over ImZnPc could also possibly be due to lower energy gap and Copper's open 3d shells as opposed to full 3d shell in Zinc which overlaps with Pc 2p shells making it more active. Graphical abstract: Image 1 Highlights: Two novel phthalocyanines, ImCuPc and ImZnPc, have been synthesized. ImCuPc had a triplet lifetime of ~1.4 μs; ImZnPc had a triplet lifetime of ~1.2 μs. The triplet quantum yields were 0.51 for ImCuPc and 0.27 for ImZnPc. ImZnPc had a larger two-photon absorption cross-section (994 GM). ImCuPc was found to possess superior n2 (3.7 × 10 −15  cm 2 /W).